International Delphi consensus on bone stress injuries in athletes - Hoenig, T.; Hollander, K.; Popp, K. L.; Fredericson, M.; Kraus, E. A.; Warden, S. J.; Tenforde, A. S. (British Journal of Sports Medicine, 2025)
Bone stress injuries, commonly referred to as stress reactions and stress fractures, represent overuse injuries to bone. These injuries result in physical limitations in activity and can be career-ending for high-level athletes. While bone stress injuries have received increased attention in recent years, international consensus is lacking on definitions, risk factors and strategies for management and prevention. This study aimed to ascertain and improve the level of agreement on bone stress injuries by utilising a three-part modified Delphi approach on (1) pathophysiology, diagnosis, terminology and classification systems; (2) risk factors, screening and prevention; and (3) management and return to sport. A multidisciplinary steering committee initiated the consensus process. A panel of 41 members from six continents was formed to complete three rounds of voting, including experts (scientists and clinicians) and representatives (athletes and coaches). Thirty-three, 28 and 28 panel members completed Delphi rounds 1, 2 and 3, respectively. Consensus was reached on 41 out of 58 statements. Findings from this Delphi study outline a multifactorial approach to identify and manage bone stress injuries and to promote bone health in athletes. This includes recommendations for diagnostic workup and treatment to assist clinicians in caring for patients with bone stress injuries. Finally, this consensus process identifies knowledge gaps and provides a framework for future research to advance the clinical care and prevention of bone stress injuries.